The Effect of Mechanical Ventilation on Peripheral Perfusion Index and Its Association With the Prognosis of Critically Ill Patients. Issue 5 (May 2019) - Su, Longxiang; Zhang, Ruiming; Zhang, Qing; Xu, Qun; Zhou, Xiang; Cui, Na; Wang, Hao; Wang, Xiaoting; Chai, Wenzhao; Rui, Xi; Liu, Dawei; Long, Yun
Abstract : Objectives: This study aimed to explore the relationship between the variables of mechanical ventilation and circulatory perfusion and its association with ICU mortality during the first day of mechanical ventilation. Design: Retrospective cohort study. Setting: The Department of Critical Care Medicine, Peking Union Medical College Hospital. Patients: Patients who have undergone mechanical ventilation. Interventions: None. Measurements and Main Results: This study used the main clinical data obtained from the real-time bedside messaging systems of mechanically ventilated patients during their first day in the ICU from May 2013 to May 2016, including data on the variables of mechanical ventilation and circulatory perfusion. An analysis was then performed on the association of the above data with the patient's in-ICU mortality. There were 5, 103 patients who received mechanical ventilation during this period, and of these, 309 patients died during their ICU treatment. Peak airway pressure, mean airway pressure, respiratory rate, heart rate, mean arterial pressure, FIO2, blood oxygen saturation, PO2, peripheral perfusion index, and lactate level were correlated with patient outcomes. A Cox logistic regression analysis suggested that mean airway pressure and perfusion index were the most independent risk and protective factors, respectively, for patient ICU mortality. The areas under the curve for a poor prognosis for mean airway pressure and perfusion index were 0.799 (95% CI, 0.77–0.829) and 0.759 (95% CI, 0.729–0.789), respectively. Further, mean airway pressure and perfusion index exhibited a causal interaction. The relative excess risk due to interaction was 2.061 (–0.691 to 4.814), the attributable proportion due to interaction was 0.210 (–0.027 to 0.447), and the synergy index was 1.306 (0.930–1.833). Conclusions: A higher mean airway pressure and lower perfusion index provided a worse prognosis in mechanically ventilated patients, and it appears that these two variables have a casual interaction. Abstract : Supplemental Digital Content is available in the text.